Annealing temperature dependence of band alignment of NiO/β-Ga2O3. (22nd September 2022) - Xia, Xinyi; Li, Jian-Sian; Chiang, Chao-Ching; Yoo, Timothy Jinsoo; Ren, Fan; Kim, Honggyu; Pearton, S J
Abstract: The band alignment of sputtered NiO on β -Ga2 O3 was measured by x-ray photoelectron spectroscopy for post-deposition annealing temperatures up to 600 °C. The band alignment is type II, staggered gap in all cases, with the magnitude of the conduction and valence band offsets increasing monotonically with annealing temperature. For the as-deposited heterojunction, Δ E V = −0.9 eV and Δ E C = 0.2 eV, while after 600 °C annealing the corresponding values are Δ E V = −3.0 eV and Δ E C = 2.12 eV. The bandgap of the NiO was reduced from 3.90 eV as-deposited to 3.72 eV after 600 °C annealing, which accounts for most of the absolute change in Δ E V −Δ E C . Differences in thermal budget may be at least partially responsible for the large spread in band offsets reported in the literature for this heterojunction. Other reasons could include interfacial disorder and contamination. Differential charging, which could shift peaks by different amounts and could potentially be a large source of error, was not observed in our samples.